State spending for higher education: Does it improve economic performance?*. Issue 1 (20th April 2017) - Bowen, William M.; Qian, Haifeng
Abstract: Increases in regional spending for higher education are conventionally believed to cause increases in economic performance. However, while some empirical evidence directly or indirectly confirms this belief, some research also brings it into question and even contradicts it. This research uses panel Granger causal models to consider not only the conventional belief but also the opposite possibility – that increases in economic performance cause increases in US state spending for higher education. It examines state spending for higher education in relation to educational attainment, per capita income and gross domestic product within the fifty states of the United States for the period 1989–2014. The results show that while increases in the share of a state's population with a bachelor degree Granger causes improved economic performance, in the short term of four years or less the direction of causality goes in the opposite direction from the one conventionally believed. Implications of this reverse causality are discussed from the policy perspective.